Answers

2016-05-25T02:02:06+08:00
   2 tan² A + 2 tan A sec A + 1   =   sec² A(1 +sin A)²
  
 LS
          2 tan² A + 2 tan A + 1          /   sec A  =  1/ cos A
                             cos A
RS
           sec² A(1 + 2 sin A + sin² A)
           sec² A + 2 sin A sec² A + sin² A sec²A
           sec² A + 2 sin A  +   sin² A       /  sin² A / cos² A    =   tan² A
                           cos² A   +  cos² A

           1 + tan² + 2 tan A + tan² A       / sec² A   =   1 + tan²
                               cos A
            2 tan² A + 2 tan A + 1
                                cos A
           so            LS  =   RS
0